Pelatihan Optimalisasi Media Sosial dalam Mendukung Kampanye Sosial dan Budaya Lokal - Wahyudi Syaputra; Uci Suriani; Rahma Fitriyani (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
The training "Optimizing Social Media in Supporting Local Social and Cultural Campaigns in Palembang City" was held with the aim of improving the understanding and skills of the community, especially cultural community actors, in utilizing social media as a tool to introduce and preserve Palembang's local culture. The background of this training is driven by the rapid development of digital technology, which opens up great opportunities for the City of Palembang to promote its rich culture and traditions to a global audience. Training activities are carried out in the form of theoretical and practical sessions, which include content creation, interaction strategies with audiences, and selection of the right platform to convey local cultural messages. The results of this training showed an increase in participants' understanding of the importance of using social media in cultural and social campaigns, as well as practical skills in creating effective content. In conclusion, this training successfully equips participants with the ability to optimize social media in promoting local culture and strengthening Palembang's cultural identity in the digital world.